2010
DOI: 10.1016/s1877-1173(10)93009-3
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Heparan Sulfate in Angiogenesis

Abstract: Heparan sulfate (HS) is a linear polysaccharide composed of 50–200 glucosamine and uronic acid (glucuronic acid or iduronic acid) disaccharide repeats with epimerization and various sulfation modifications. HS is covalently attached to core proteins to form HS-proteoglycans. Most of the functions of HS-proteoglycans are mediated by their HS moieties. The biosynthesis of HS is initiated by chain polymerization and is followed by stepwise modification reactions, including sulfation and epimerization. These modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 141 publications
2
59
0
Order By: Relevance
“…HSPGs are expressed on the EC surface where they act as low-affinity receptors for circulating growth factors and chemokines (26). HSPGs were found to critically regulate angiogenesis by facilitating cell-surface binding of various proangiogenic molecules (27). Recent data showed that p17 is a heparin/heparan sulfate-binding protein (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPGs are expressed on the EC surface where they act as low-affinity receptors for circulating growth factors and chemokines (26). HSPGs were found to critically regulate angiogenesis by facilitating cell-surface binding of various proangiogenic molecules (27). Recent data showed that p17 is a heparin/heparan sulfate-binding protein (28).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study pointed to the capability of p17 to bind to HSPGs (28) and HSPGs are known to play a proangiogenic role depending on heparan sulfate fine structure (26,27). However, treatment of HUVECs with heparinase II to remove HSPGs did not influence the ability of p17 to form capillary-like structures.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into the molecular mechanism underlying the angiogenic defect in Ndst1 ECKO mice, we initially speculated that endothelial Ndst1 deficiency might disrupt VEGF signaling, based on our previous findings that endothelial Ndst1 deletion attenuates VEGF signaling in tumor angiogenesis (9,14). However, examination of VEGFR2 phosphorylation found no significant difference between Ndst1 ECKO and Ndst1 f/f diaphragm at E18.5 ( Figure 4A).…”
Section: Mice Deficient In Endothelial Ndst1 Develop Postnatal Cdh Nmentioning
confidence: 99%
“…A perturbation of HSPGs can result in a variation of morphogen gradients in ECM or alternatively it can interfere with stabilization of signaling complexes. 43 To test this hypothesis, we perturbed the overall HSPGs maturation by injecting a previously published MO targeting HS6ST2 34 . Sulphotransferases contribute to the heterogeneity of heparan sulphates and ECM maturation, which is essential for the modulation of ligand-receptor binding.…”
Section: β-Nrxn1a and Nlgn1 Are Involved In Cp Formation In Synergy Wmentioning
confidence: 99%